Enhancing UHPC beam performance with GFRP sheets - Nur Fisni Mohamad Fuad; Adiza Jamadin; Sakhiah Abdul Kudus; Mohamad Farid Misnan; Hasan Ali Abbas (Penerbit Universiti Kebangsaan Malaysia, 2024)
A cement-based composite, ultra-high-performance concrete (UHPC) helps both new and old buildings last longer in service. The growing demand for quality building materials and applications has led to the emergence of various commercial UHPC formulations after decades of research and development. Nevertheless, they are costly and necessitate strict design specifications. Infrastructure like bridges commonly experience structural vibration and static loads during traffic congestion, which can reduce their service life. This study examines the impact of the length and pattern of Glass Fibre Reinforced Polymer (GFRP) sheets wrapped around UHPC beams to strengthen them. The tested UHPC beams had dimensions of 100 × 100 × 500 mm. One beam was tested without GFRP reinforcement, while six beams with various GFRP patterns were subjected to a four-point loading test. The study assessed the initial fracture load, energy absorption, deflection, and ultimate load capacity. Compared to unwrapped beams, the experimental results indicated that GFRP-wrapped beams exhibit substantially higher initial and final load-carrying capacities. The results reveal that GFRP reinforcement can greatly enhance the longevity and structural efficiency of UHPC beams